Developmental time of immature forms of Sabethes aurescens Lutz (Diptera, Culicidae) from artificially perforated bamboo in the rain forest of southern Brazil - Muller,Gerson Azulim (2009)
The development time of the immature forms of Sabethes aurescens Lutz, 1905, from perforated bamboo in the southern Brazil rain forest was studied under laboratory conditions. Mean development periods were 5±2.23, 10±5.20, 14±8.26, 36±13.90 and 9±2.43 days, respectively, for the four larval instars and pupae. The 4th instar of females was longer than that of males. Implications of the long development time of the immature forms of Sa. aurescens are discussed.